PRIVASI DAN KEAMANAN DATA DALAM LAYANAN CLOUD: PERSPEKTIF HUKUM DAN REGULASI - Hertawaty Sijabat, Hotmaria; Widjaja, Gunawan (Penerbit Lafadz Jaya, 2025)
The use of cloud services has become increasingly common in recent years, but this brings significant challenges related to data privacy and security. This paper examines the legal and regulatory perspectives on data privacy and security in cloud services. With regulations such as the General Data Protection Regulation (GDPR) in the European Union, strict standards have been set to protect personal data. The responsibility for ensuring data privacy and security must be shared between cloud service providers and users, with clear policies and contracts defining their respective responsibilities. Furthermore, as technology advances rapidly, regulations must continue to evolve to address new challenges and ensure adequate data protection. International collaboration and increased technological awareness among policymakers are also key factors in this effort.